‘Crafting Self-Identity in a Virtual Community’ - Yan Wu (Multicultural Education & Technology Journal, 2007)
To study the process of constructing self identity by Internet users is achallenging task for social scientists, while the use of ethnographic method instudying the interactions among individuals in an online virtual community is byno means of easy job. Employing qualitative studies as the main researchapproach, the authors conducted a case study of the Qiangguo Luntan, a virtualcommunity for the mainland Chinese, with a focus on its users’ identitiesconstructed politically. The paper examines the users’ pennames, signature files,online behaviours such as lurking and flaming and political clusters formed ondifferent ideological viewpoints and argues that Internet bulletin boards asvirtual communities in China are used as social institutions in the public spherealthough this virtual public sphere still has its limitations in terms ofinclusiveness, autonomy, and people’s public use of their reason.